Hearing Loss and Middle Ear Effusion in Nasopharyngeal Carcinoma Following Radiotherapy: Dose–Response Relationship and Normal Tissue Complication Probability Modeling - Prem Wungcharoen; Anussara Prayongrat; Napadon Tangjaturonrasme (International Archives of Otorhinolaryngology)
Introduction Radiotherapy is the primary treatment for nasopharyngeal carcinoma. Radiation exposure to the cochlea and middle ear can cause hearing loss.